Exercise-induced fatigue: Exploring mechanisms and counter strategies - Abdul Manaf, F. (Murdoch University, 2017)
Mechanisms leading to fatigue have been the subject of immense research investigation. However, the exact mechanisms causing the development of fatigue, remain largely unknown and fiercely debated. Herein we identify plasma metabolites and neuromuscular factors associated with exercise-induced fatigue, and assess potential nutritional strategies which may help delay the onset of fatigue. The role of individual metabolites in the development of fatigue were assessed using metabolomic profiling of plasma during a constant endurance cycling bout in Chapter 3. Analyses revealed important associations between fatigue-onset with free fatty acids, tryptophan and glucose. The contribution of central- and peripheral fatigue mechanisms during isoenergetic constant and self-paced cycling trials was assessed in Chapter 4. Central fatigue was similar following each protocol, but total fatigue was shown to be greater following self-paced cycling. Importantly, the serotonin precursor tryptophan has been implicated in the onset of fatigue, and tryptophan is displaced from albumin when lipid concentrations iincrease; this may explain the association between increased lipid concentration and fatigue observed in Chapter 3. Therefore, using a branched-chain amino acids (BCAA) supplement, we manipulated the free-tryptophan (unbound) passage across the blood brain barrier (Chapter 5). We observed greater endurance capacity with the BCAA compared to a placebo, although this was independent of changes in central fatigue. In an attempt to mitigate the decrease in blood glucose concentrations in endurance cycling (observed in Chapter 3), a mixed-carbohydrate comprising starch and disaccharides was ingested before and immediately after a prolonged cycling bout(Chapter 6). We hypothesised that this mixed-carbohydrate beverage would minimise hypoglycaemia when compared to an isocaloric glucose beverage and improve overall performance. Although blood glucose and insulin were significantly different between conditions, there were no differences in exercise performance or fatigue markers between conditions. The significance of these findings and future directions of research are discussed in Chapter 7.